(untitled) (Journal of Educational Sciences, 2016)
XXI century is the century of information technologies. Distance learning is a method of distance education, where teacher and students are physically located in different places. Technology implementation of the remote form of training: case – printed materials, audio and video lectures, interactive computer training, electronic textbooks, multimedia tools, hypermedia means, electronic (virtual) library, the Internet and computer control systems, Web-TV (video conferencing). System approach includes consideration of all components of distance education: methodological, pedagogical, methodological, economic, organizational. In the survey revealed the advantages of distance learning students. The article reveals the important components of the electronic University: personal offi ce student, private offi ce of a teacher, corporate electronic control. The advantages of distance learning technologies, lists actual problems of distance education development in Kazakhstan. Distance learning can contribute to the building of a new educational model.